Teacher Factors as a Mediator between Teaching and Testing at the Higher Education Level - Athiworakun, Chuenjit; Adunyarittigun, Dumrong (rEFLections, 2024)
The washback effects of high-stakes tests have become conspicuous and prevalent in Thai educational contexts. Yet, researchers in language assessment still have much to strive towards to understand the nuanced role of teacher factors as a mediator between the washback effects of high-stakes tests and teaching. This study aimed to investigate how teacher factors mediated between the Srinakharinwirot University Standardized English Test (SWU-SET), an exit examination for undergraduate students at a Thai public university in Thailand, and teaching. A mixed-methods design was implemented in this study. The researchers asked 25 full-time university teachers to complete a questionnaire, and five of them were purposively selected to be the informants for an interview and reflective journals. Descriptive statistics and content analysis were employed for data analysis. The main findings revealed that teacher factors (i.e., knowledge, beliefs, and experience) mediated between the SWU-SET and teaching. A smorgasbord of teacher knowledge of such tests and assessment literacy, beliefs in test writer integrity and professionalism, and experience in test development and taking tests could help induce the intended washback. Finally, this study also proposed a model of mediating factors and the washback effects of the SWU-SET on teaching to help stakeholders make informed decisions on teaching.